Ilmu jiwa: prinsip prinsip dan implementasinya dalam pendidikan - Abdul Aziz El_Quussy (Bulan Bintang, 1976)
ir, jil.1,c.1-2/tr, jil.1=c.3-11/ir, jil.2=c.1-2 ; jil.3=c.1-3/tr, jil.1=c.12/en, c.3/en, jil.2=c.4-5/en, jil.3=c.4-5/en, .jil.1=c.13-14/en, jil.3=c.6/en,.jil.2=c.6